2020
DOI: 10.3390/pr8101210
|View full text |Cite
|
Sign up to set email alerts
|

New Insights on Protein Recovery from Olive Oil Mill Wastewater through Bioconversion with Edible Filamentous Fungi

Abstract: Olive oil mills represent an important sector in the Mediterranean Sea Basin but also an environmental hazard due to untreated wastewater. Recovery of nutrients from olive oil mill wastewater (OMWW) as protein-rich microbial biomass can produce novel feed and reduce its chemical oxygen demand; however, low-protein containing products have been reported. New strategies leading to higher protein-containing fungal biomass could renew the research interest on bioconversion for pollution mitigation of OMWW. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 42 publications
0
26
0
Order By: Relevance
“…The highest amount of biomass (2.16 g/L, Figure 1) was obtained in the medium of VFA effluents from the CKM containing the highest total VFAs (Table 1). High carbon content might have a positive effect on biomass production, and the initial pH and nitrogen content of the medium also have a critical role in fungal growth and sporulation and cultivation yield [17,[27][28][29].…”
Section: Biomass Cultivation In Flask Vs Bubble Column Reactormentioning
confidence: 99%
See 3 more Smart Citations
“…The highest amount of biomass (2.16 g/L, Figure 1) was obtained in the medium of VFA effluents from the CKM containing the highest total VFAs (Table 1). High carbon content might have a positive effect on biomass production, and the initial pH and nitrogen content of the medium also have a critical role in fungal growth and sporulation and cultivation yield [17,[27][28][29].…”
Section: Biomass Cultivation In Flask Vs Bubble Column Reactormentioning
confidence: 99%
“…In addition, it was found that the VFAs obtained from the mixture of CM with FW, whose C/N ratio was much higher than the others (except for FW), was preferable for the growth of A. oryzae, achieving a higher biomass production yield of 0.37-0.47 g dry biomass/gCOD eq.consumed (Table 2), whereas the amount of fungal biomass produced in this mixture medium was relatively lower than in the other media. Similarly, the biomass production efficiency was increased by adding nitrogen such as ammonia, ammonium sulfate or sodium nitrate to balance the C/N ratio [17,32,33].…”
Section: Biomass Cultivation In Flask Vs Bubble Column Reactormentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, OMWW can serve as a substrate for edible filamentous fungi, which can be used as a protein source. However, the process still needs to be optimized to increase the production of fungal proteins above the 15% yields currently achieved [ 92 ].…”
Section: Emerging Food Technologies For Increasing the Sustainabilmentioning
confidence: 99%